POSHAN's abstract digest on maternal and child nutrition research - Issue 25 - Avula, Rasmi (International Food Policy Research Institute, 2018)
This issue of Abstract Digest is special indeed. We have put together a selection of articles from a couple of journal supplements, along with other interesting articles.